Split-Half Analysis : Measurement of Validity and Reliability of the Career Counselling Self-Efficacy Scale (CCSES) in Malaysian Public Universities - Edris, Bin Aden; Amat, S.; Mahmud, M. I.; Abu Bakar, A. Y.; Nor Mazlina, Binti Ghazali; Azzahrah, Binti Anuar (IJICC, 2019)
Self-efficacy is an important aspect in measuring counsellor’s abilities to conduct counselling processes. This study aims to assess the validity and reliability of self-efficacy using the Split-half technique. The Career Counselling Self-Efficacy Scale (SSES) aims to measure the level of counsellor’s readiness to provide career counselling services to clients that covers aspects of knowledge and skills. A quantitative approach was used and data analysed by using the SPSS. The instrument has been translated into Malay and involved a 25 items instrument consisting of five sub-scales related to the counsellor’s efficacy. The analysis using the Split-half approach reported the reliability value for the entire item of Part 1 (0.96) and Part 2 (0.97). The study has inferred that the instrument has a satisfactory level of reliability and can be used in the Malaysian context. The new version of instruments has an impact to the counsellor competency in practice. The counsellor will have a view in terms of their ability to handle career counselling. Aside from curriculum development, career counselling can be improved in line with current need. There are a limited numbers of inventories translated into Malay. The new version of CCSES can minimise the cultural issues faced by counsellors in their practice.